2015
DOI: 10.1021/acsnano.5b00121
|View full text |Cite
|
Sign up to set email alerts
|

Intumescent Flame-Retardant and Self-Healing Superhydrophobic Coatings on Cotton Fabric

Abstract: Flame-retardant and self-healing superhydrophobic coatings are fabricated on cotton fabric by a convenient solution-dipping method, which involves the sequential deposition of a trilayer of branched poly(ethylenimine) (bPEI), ammonium polyphosphate (APP), and fluorinated-decyl polyhedral oligomeric silsesquioxane (F-POSS). When directly exposed to flame, such a trilayer coating generates a porous char layer because of its intumescent effect, successfully giving the coated fabric a self-extinguishing property. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
276
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(284 citation statements)
references
References 32 publications
6
276
0
2
Order By: Relevance
“…The use of nanoscale fillers in paper coatings nowadays mainly focuses on the use of inorganic pigments [5], minerals [6], ceramics [7], while bio-based nanofillers such as nanocellulose [8] and nanoclays [9] were more recently considered. Several interesting functionalities attained by employing nanomaterials include, antimicrobial paper [10], microfluidic paper devices [11], bioactive papers for drug delivery [12], flame-retardant papers or self-healing properties for cotton fabric [13]. However, the compounding of bio-based nanocomposite coatings is frequently hindered by a homogeneous dispersion of the fillers within the matrix and (mass-) production by fast and cheap processing of nanocomposite coatings remains limited, as it is often done by casting rather than continuous processing.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanoscale fillers in paper coatings nowadays mainly focuses on the use of inorganic pigments [5], minerals [6], ceramics [7], while bio-based nanofillers such as nanocellulose [8] and nanoclays [9] were more recently considered. Several interesting functionalities attained by employing nanomaterials include, antimicrobial paper [10], microfluidic paper devices [11], bioactive papers for drug delivery [12], flame-retardant papers or self-healing properties for cotton fabric [13]. However, the compounding of bio-based nanocomposite coatings is frequently hindered by a homogeneous dispersion of the fillers within the matrix and (mass-) production by fast and cheap processing of nanocomposite coatings remains limited, as it is often done by casting rather than continuous processing.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach has no healing effect on the physical damage to the surface microstructures. Until now, very few studies have reported superhydrophobic coatings with self-healing surface microstructures [22][23][24] . Lynn et al prepared a water-assisted self-healing superhydrophobic coating using layer-by-layer assembly.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, the most widely known example is the lotus leaf owing its self-cleaning properties due to the coexistence of micro-nanostructure and low surface energy waxy coating that weakens the electrostatic interaction between water and surface [1]. Due to the versatile applications of superhydrophobic surfaces researchers all around the world is are continuously working in this field of research [2][3][4][5][6]. Our group is actively working in the fabrication of superhydrophobic surfaces on aluminum and other metal surfaces using different techniques [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%